A Measure of the Severity of Depressions, 1873-1932 - Eckler, A. Ross (The Review of Economics and Statistics, 1933)
T HE various trade and production indexes which have been compiled during recent years are valuable in furnishing students of economic history with a continuous record of the fluctuations of general business. To mention a few such indexes, Colonel Leonard Ayres has compiled an index of general business extending backto I790; the Index of Industrial Production and Trade prepared by Dr. Warren Persons covers the years since I875; and the American Telephone and Telegraph Company has a compositeindex of business activity from I877 to date. In the case of these averages, as well as of some others that might equally well have been mentioned, the purpose has been to secure a continuous record of the general economic situation in the United States. By the use of one or more of these compilations the relative magnitudes of cyclical movements may be compared. It is to be assumed that the element of long-time growth has been carefully measured 'and eliminated, and therefore, in order to measure the relative severities of depressions, or the relative intensities of booms, it should theoretically be necessary only to compare (in some manner or other) the displacements from the normal line. Such an approach, however, lacks objectivity, for the choice of a line of trend may be based in part upon the reasonableness of the degree of 'prosperity and depression that it indicates. The determination of the secular trend of an economic series is never wholly a precise mathematical operation; moreover, the fixing of the normal level for a given year is probably somewhat more dependent upon personal judgment than is the determination of the normal rate of increase. It seems desirable, accordingly, to utilize a more direct approach to the problem of measuring the amplitude of cyclical movements in this country. An examination of the size of the fluctuations occurring in the most important series of business data should throw some light upon the character of cyclical down-turns, and should prove useful in supplementing the story presented by the several composite indexes. Such an examination, if based upon monthly items, would be greatly handicapped by the scarcity of series extendingback more than fifty years. For annual series, on the other hand, the amount of available material is large. It is not necessary here to recount the advantages and disadvantages involved in the use of annual data. It is perfectly clear that for certain kinds of analysis yearly figures are far inferior to monthly. In particular, they are not satisfactory for the determination of time relationships among series in cases when the lags are in terms of months rather than of years. The conclusion, however, that annual data cannot serve a useful purpose in recording the magnitudes of cyclical movements does not seem warranted. On the contrary, it appears likely that any business decline important enough to be recognized by economic historians would be definitely noticeable in the annual record of almost every series relating to important business activities. This should be equally true whether the valley of the depression was shallow and wide, or deep and narrow. During periods of rapid growth, of course, it might happen that a mild down-turn would be reflected merely in the failure of the series to achieve more than a part of 'its full normal year-to-year increase. For the' measurement of such minor declines, annual data may often prove less dependable than monthly items. On the other hand, the use of yearly figures brings certain definite advantages in the measurement of cydes over a-long period of years. It makes available a much larger number of series upon which the investigator may base compan'sons. ' In addition, it automatically eliminates the problem of determining seasonal movements, and thus increases the objectivity of the results. Our choice of the period to be examined was based in large part upon economic considerations. From the point of view of American economic history, the years since I870 possess a sufficient amount of economic homogeneity to render appropriate the comparison of business conditions and tendencies. Numerous comparisons of the present situation with that in the seventies and in the nineties, revealing considerable similarities, have been made. Comparisons with the panics of I837 and of I857 are much less frequent, and are made with the realization that the United